Ālūra Veṅkaṭarāv - Huyilagōḷa, Varadarāja (Sāhitya Akādemi, 2007)
On the brief life and works of Alūra Veṅkaṭarāva, 1880-1964, Kannada scholar
Includes bibliographical references. - Kannada in kanares. Schr
Keywords: Biografie; Veṅkaṭarāva; Ālūra 1880-1964; Authors; Kannada